Generation of multicolor banding probes for chromosomes of different species - Kosyakova, Nadezda (BioMed Central, 2013)
BACKGROUND: The multicolor banding (MCB/mBAND) technique provides a unique opportunity to characterize intrachromosomal rearrangements and to determine chromosomal breakpoints. Until recently, MCB probes have only been available for human and some murine chromosomes. Generation of MCB probes for chromosomes of other species, useful and required in many cytogenetics research fields, was limited by technical difficulties. MCB probes are established by chromosome microdissection followed by whole genomic DNA amplification. However, unambiguous identification of the target chromosome is required for MCB-probe establishment. Previously proposed protocols suggested G-banding staining or preliminary FISH with whole chromosome paints (WCP) as methods to identify the chromosome of interest. RESULTS: Here we present a complete workflow for MCB probe generation for those cases and species where chromosome morphology is too challenging to recognize target chromosomes by conventional methods and where WCP probes are not available. The workflow was successfully applied for murine chromosomes that are difficult to identify unambiguously. Additionally, we showed that glass-needle based microdissection enables establishment of a whole set of WCP paints by microdissection of individual chromosomes of a single metaphase CONCLUSIONS: The present method can be applied for generation of whole or region-specific DNA probes for species, where karyotyping of G-banded chromosomes is challenging due to similar chromosome morphology and/or chromosome banding patterns.